Cywilizacja miłości wobec kultury konsumpcyjnej. Wybrane zagadnienia filozofii społecznej papieża Jana Pawła II (Przegląd Religioznawczy – The Religious Studies Review, 2020)
This article is an attempt to present the program of the „civilization of love” in the context of the cultural strategy implemented by John Paul II. The above strategy is aimed at, inter alia, against tendencies unfavourable for the Church. On the one thing, it is „humanism without God”, an „inauthentic culture” based on false ontology and anthropology. On the other hand, it is a contemporary globalized world, consumed by market ideology, an economism promoting consumer identity. According to John Paul II, there are essential elements of an „inauthentic culture”, of departing from God, promoting values without reference to transcendence. The culture of consumerism is a culture of subjective truths that implement individual and selfish social projects, negating the implementation of the Christian doctrine of the common good, the „civilization of love”.